Financial Effects of Different Amortization Methods of the Enterprise’s - Alina Zając (Contemporary Economics)
Every enterprise could lead economic activity and has to possess suitable material base, which makes up first of all the productive potential, consisting mainly with centers of production, and so the centers of work ( the buildings, machine and the device) and the objects of work ( the materials). It is individual subject gradual waste of that is amortization property. Amortization is reflection in track of peeled period of exploitation their waste, but simultaneously making up cost has influence on formation the financial result of the enterprise.